Problematika Pelayanan Kesejahteraan Sosial Di Kecamatan Trumon Kabupaten Aceh Selatan - Ramazan, Syahril (JAROW: Journal of Ar-Raniry on Social Work, 2025)
This study is entitled Problems of Social Welfare Services in Trumon District, South Aceh Regency. Problems of social welfare services are a problem that often occurs in all processes of social welfare services to the community, including in Trumon District, South Aceh Regency. This study aims to determine the problems, obstacles, and solutions to the problems of social welfare services in Trumon District. The research method used in this study is qualitative with data sources from in-depth interviews and participatory observations of the South Aceh District Social Service, Trumon District Government, Kasi Puspelkesos Trumon, TKSK Trumon, Imum mukim and other related parties as well as documentation as a source of strengthening research in Trumon District. The results of this study indicate that various problems of social welfare services in Trumon District have fundamental problems, namely the absence of professional social workers in providing social welfare services. This has implications for all aspects of service, both in terms of communication, handling, and service in the context of social welfare. The obstacles that occur lead to the government's attention sector which is very minimal in the form of budget and logistics. The solution to the problems that occur is the need for reform in terms of the placement of service human resources so that social welfare services in the Trumon sub-district occur properly, apart from that the government is required to provide full service to social welfare.